Odpowiedź :
a - krótsza przyprostokątna
b = 3 a - dłuższa przprostokątna
c = 20√5 cm - przeciwprostokątna
Z Pitagorasa:
a² + b² = c²
Podstawiamy:
a² + (3a)² = (20√5 cm)²
10 a² = 2 000 cm²
a² = 200 cm²
a = 10√2 cm
b = 3a = 30√2 cm
Pozdro))
b = 3 a - dłuższa przprostokątna
c = 20√5 cm - przeciwprostokątna
Z Pitagorasa:
a² + b² = c²
Podstawiamy:
a² + (3a)² = (20√5 cm)²
10 a² = 2 000 cm²
a² = 200 cm²
a = 10√2 cm
b = 3a = 30√2 cm
Pozdro))
3x-dłuższa
x-krótsza
z pitagorasa
(3x)²+x²=(20√5)²
9x²+x²=400x5
10x²=2000
x²=200
x=√200 - dł krótszej
3x=3√200 - dł dłuższej
x-krótsza
z pitagorasa
(3x)²+x²=(20√5)²
9x²+x²=400x5
10x²=2000
x²=200
x=√200 - dł krótszej
3x=3√200 - dł dłuższej